NILAI RELIGIUS DALAM NOVEL DAUN PUN BERDZIKIR KARYA TAUFIQURRAHMAN AL-AZIZY DAN RENCANA IMPLEMENTASINYA - Nurdiani Nurdiani; Martono Martono; Christanto Syam (Universitas Tanjungpura, 2020)
AbstractThis research is motivated by the activities of researchers to find various values, one of which is religious value. Problems in research regarding the religious value of human relations with God, humans with fellow humans, humans with themselves, and the implementation of literary learning in schools. The method used in this research is descriptive method and this research is in the form of qualitative. The approach used in this research is the sociology of literature approach. The technique used in this research is documentary study technique. The data source in this study is a novel entitled Daun Pun Berdzikir by Taufiqurrahman Al-Azizy. The data in this study are religious values in the form of words, phrases and sentences contained in the novel Daun also Berdzikir by Taufiqurrahman Al-Azizy. The results showed that the relationship between humans and God included believing in God, praying and praying, believing that death was Gods will, surrender to God, an a match in Gods hands. Human relations with fellow humans including, mutual cooperation, please help, and affection. Human relations with themselves include, emotions, obedient to the commands of parents, patient, humble, brave, honest, diligent, have a strong desire, fell compassion for others, not easily discouraged, and obedient. These values are important to apply in everyday life. Keywords: implementation plan, learning, novels, religious values